2017
DOI: 10.3892/mco.2017.1215
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoid adenocarcinoma of the lung metastasizing to the tonsil

Abstract: Abstract. Hepatoid adenocarcinoma (HAC) is a rare tumor that typically originates in gastrointestinal tissue, such as the stomach, but can also occasionally originate in the lung. The majority of HACs express α-fetoprotein (AFP) on tumor cells, and serum AFP can be used as a marker of response to treatment or disease progression. HAC has a poor prognosis, although early diagnosis and aggressive treatment can result in long-term survival. To the best of our knowledge, this is the first reported case of HAC meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…Neoadjuvant chemotherapy plus surgical resection could be used to treat non-advanced HAL, whereas the regimens for advanced-stage patients have not been established. [1][2][3][11][12][13][14][15][16][17][18][19][20][21][22][23][24] We searched all known cases of HAL and included a total of 22 patients who were treated with chemotherapy and immunotherapy in the literature review (Table 2). Interestingly, most of the patients were male (20/22) and only 2 female cases (including the present case) were reported which indicated a sex difference of HAL.…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant chemotherapy plus surgical resection could be used to treat non-advanced HAL, whereas the regimens for advanced-stage patients have not been established. [1][2][3][11][12][13][14][15][16][17][18][19][20][21][22][23][24] We searched all known cases of HAL and included a total of 22 patients who were treated with chemotherapy and immunotherapy in the literature review (Table 2). Interestingly, most of the patients were male (20/22) and only 2 female cases (including the present case) were reported which indicated a sex difference of HAL.…”
Section: Discussionmentioning
confidence: 99%
“…The second is that neither a high serum AFP level nor the tumor AFP expression directly results in a poor prognosis. 5,6,17 In the current case, the cancer was aggressive, and the patient died six months after the initial diagnosis regardless of the tumor's negative expression of AFP. Therefore, hepatoid morphology is the most important factor for diagnosing hepatoid adenocarcinoma of the lung.…”
Section: Discussionmentioning
confidence: 63%
“…Hepatoid adenocarcinoma of the lung is a rare subtype of lung carcinoma, and only 22 cases have been reported in the full-text English literature. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Ishikura et al, 20 first reported a hepatoid adenocarcinoma of the lung and proposed the following two diagnostic criteria: (i) presence of typical acinar or papillary adenocarcinoma, and (ii) presence of a carcinoma component which resembles hepatocellular carcinoma and produces AFP. However, only 12 out of 23 (52.2%) hitherto described cases exhibited high serum AFP levels (>10 ng/ml).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the reported cases, the clinical features, treatments and prognosis of the pulmonary HAC patients are shown in Table 1 (palliative radiotherapy to bone or other metastatic sites is not included in the table). 1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The incidence of pulmonary HAC is higher in men, which is similar to the incidence of other pathological types of lung cancer. The age of the patients ranges from 47 to 71, with an average age of 58.91 years.…”
Section: Discussionmentioning
confidence: 87%